Radioactive Waste Engineering and Management - Nagasaki, Shinya (Springer, 2015)
This book describes essential and effective management for reliably ensuring public safety from radioactive wastes in Japan. This is the first book to cover many aspects of wastes from the nuclear fuel cycle to research and medical use, allowing readers to understand the characterization, treatment and final disposal of generated wastes, performance assessment, institutional systems, and social issues such as intergenerational ethics. Exercises at the end of each chapter help to understand radioactive waste management in context.